Effects of orally administered lactoferrin and lactoperoxidase on symptoms of the common cold - Shin, Kouichirou; Wakabayashi, Hiroyuki; Sugita, Chihiro; Yoshida, Hiroki; Sato, Keizo; Sonoda, Tohru; Yamauchi, Koji; Abe, Fumiaki; Kurokawa, Masahiko (International Journal of Health Sciences, 2018)
Objectives: Lactoferrin (LF) and lactoperoxidase (LPO) are present in human saliva. LF has been demonstrated to show antibacterial and antiviral activities. In saliva, LPO catalyzes the hydrogen peroxide-dependent oxidation of thiocyanate to hypothiocyanite that exhibits antimicrobial and antiviral properties. A randomized, open-label, parallel-group clinical trial was conducted to examine the effectiveness of sucking tablets containing LF and LPO (LF+LPO) in alleviating symptoms of the common cold and/or influenza infection. Methods: A total of 407 subjects were randomized into two groups, treatment and non-treatment groups, and each group was further classified into subgroups habitually wearing a face mask, washing their hands, or gargling. The common cold, influenza, and gastrointestinal symptoms were used to evaluate the effectiveness, and the incidence and duration of symptoms were statistically analyzed. Results: The incidence and duration of common cold, gastrointestinal symptoms, and influenza infection were not statistically different between treatment and non-treatment groups. LF+LPO tablets were moderately effective in reducing the incidence and duration of common cold symptoms in the subgroup that did not gargle and especially to shorten significantly the duration of fever higher than 38°C in the subgroup that did not wear a face mask. Conclusion: The results suggested that the effect of ingestion of the tablet is not obvious in alleviating common cold symptoms but may be helpful when the subjects do not follow precautionary measures such as gargling and the use of a protective face mask.